FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PUBLIK PADA KANTOR DISTRIK HINGK KABUPATEN PEGUNUNGAN ARFAK PROVINSI PAPUA BARAT - Rezky, Amelia; Adil, Muh. (COMPETITIVENESS, 2018)
To know and analyze the influence of organization, leadership, ability and skills as well as appreciation and recognition of the quality of public services in the Hingk District Office of Arfak Mountain District, West Papua Province. This research uses the form of survey research. In this study, the population is a community that takes care of a type of service at the Hingk District Office of Arfak Mountain District of West Papua Province and government employees as service providers at the Hingk District Office of Arfak Mountain District of West Papua Province. Samples are determined by saturated sampling techniques (census), i.e. all populations are sampled at the Hingk District Office of Arfak Mountain District of West Papua Province. So that the total sample as many as 48 people. Data analysis using multiple regression analysis.The results showed that there is a positive and significant influence between the organization, leadership, ability and skills as well as appreciation and recognition of the quality of public services in the Hingk District Office of Arfak Mountain District of West Papua Province. Keywords: Organization, leadership, ability, skills, appreciation, recognition, quality of service